A Study of Use of "PORT" Catheter in Patients with Cancer: A Single-Center Experience. (22nd February 2017) - Madabhavi, Irappa; Patel, Apurva; Sarkar, Malay; Anand, Asha; Panchal, Harsha; Parikh, Sonia
Background: Effective and reliable venous access is one of the cornerstones of modern medical therapy in oncology. Materials and methods: This is a prospective observational study, which collected data of patients who require "PORT" catheter insertion for any cancer, at a tertiary care oncology hospital in Ahmadabad, Gujarat, India, during a 2-year period. Aims and objectives: The main objective of this study was to study the various complications and outcomes related to "PORT" catheters. Results: "PORT" catheter was inserted in 100 patients and was most commonly used in solid malignancies (n = 86, 86%), followed by hematologic malignancies (n = 14, 14%). Among the solid malignancies, breast cancer (38, 38%) was the most common underlying disease, whereas among the hematologic malignancies, acute lymphoblastic leukemia (6, 6%) was the most common underlying disease for "PORT" catheter insertion. Chemotherapy was started on the first day of "PORT" catheter in 74% of patients in the "PORT" study group. The various complications developed in the "PORT" study group in the descending order are as follows: 4 patients (4%) developed early infection (⩽30 days after "PORT" placement), 4 (4%) late infection (⩾30 days after "PORT" placement), 4 (4%) bloodstream infection, 2 (2%) local skin infection at the "PORT" insertion site, 2 (2%) dislodgment of the "PORT" catheter, 2 (2%) fracture of the "PORT" catheter, and 1 recurrent pleural effusion. One patient (1%) developed thrombosis as the complication of "PORT" catheter insertion. Conclusions: The most disturbing aspect of treatment for a patient with cancer is multiple painful venipunctures made for administration of cytotoxic agents, antibiotics, blood products, and nutritional supplements. The focus of this prospective observational research is to study the various underlying diseases for which "PORT" catheter is needed in different solid and hematologic malignancies and the various complications and outcomes in pediatric and adult patients with cancer.